Mediation and Dialogue: New Challenges for History Textbooks - Julkowska, Violetta (Sensus Historiae, 2026)
This volume of *Sensus Historiae* offers reflections on issues relevant to the contemporary transfer of historical knowledge in schools through the use of history textbooks. Despite the rapid development of digital technology, textbooks remain the most important medium for historical content and a universal teaching tool for developing historical thinking skills. Volume LXII of “Sensus Historiae” offers a reflection on an issue less frequently addressed by historians, namely the mediating role of the didactic transmission of history, which transcends entanglement in current issues of historical politics and draws upon practices of dialogue.